Resonant impulses - Haapala, Sami Henrik (My University, 2019)
On this page you can access a short video trailer which summarizes the workshop of The Real Health Center which was realized in August 2017 in a public space in Helsinki. The clip aims to give a short, but broad view of the whole workshop. The other videos in this exposition highlight other resonant aspects of the research. This exposition exposes the second artistic part of an artistic doctoral thesis. The research questions are: Main research question: How can a performer co-create meaning together with the participant in participatory and immersive performances? Research question for this artistic part: How can we train a performer for participatory and immersive performances in which they will have to work with the unpredictable impulses of unknown audiences? This research exposition shows a distinctive approach to performer training that uses play testing with an unknown audience as a training method. This training method was developed in order to train performers in participatory and immersive performances to the specific kind of unpredictable impulses that arise from performing with unknown audience members. The exposition aims to reveal the method by transposing discursive knowledge gained from/in/by research in these kinds of performances to an online exposition that in its form and manner of presentation would resonate with some of the qualities associated with participatory and immersive performances.
Keywords: immersiivinen teatteri; Acting--Study and teaching.; Participatory theater.; taiteellinen tutkimus; näytteleminen; opetus; teatteritaide; osallistava teatteri; konstnärlig forskning; skådespelarkonst; undervisning; teaterkonst; delaktiggörande teater